2017
DOI: 10.3390/app7020175
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Natural Ventilation-enabling Façade Noise Control Devices for Congested High-Rise Cities

Abstract: Abstract:This review summarizes the current status of the research and development of natural ventilation-enabling noise control devices for use on the façades of high-rise residential buildings in congested cities. These devices are important for a sustainable urbanized city, as they are supposed to offer good acoustical protection to citizens, allowing for an acceptable level of natural ventilation inside residential units; energy for mechanical ventilation can then be saved. From the information presented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…In the following paragraphs, available noise control strategies for enabling NV are presented. Here, solutions described in the two major reviews by De Salis et al, in 2002 [19] and Tang, in 2017 [20] are briefly summarized and integrated with references to the latest available studies, differentiating between passive, active, automation-based, and hybrid solutions.…”
Section: Façade Noise Control Strategies Enabling Nvmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following paragraphs, available noise control strategies for enabling NV are presented. Here, solutions described in the two major reviews by De Salis et al, in 2002 [19] and Tang, in 2017 [20] are briefly summarized and integrated with references to the latest available studies, differentiating between passive, active, automation-based, and hybrid solutions.…”
Section: Façade Noise Control Strategies Enabling Nvmentioning
confidence: 99%
“…The indoor-outdoor connection they provide has been, so far, a major limiting factor in the use of NV due to the conflict between ventilation needs and the intrusion of external noise, which impedes naturally ventilated buildings from meeting background noise limits set by acoustic standards, building design regulations and rating protocols. As a response, for a long time, research has been developing a number of solutions that try to guarantee ventilation without compromising façade noise insulation [19][20][21][22][23][24]. Each of them presents advantages and disadvantages, but, up to the now, none has taken hold on large scale.…”
Section: Introductionmentioning
confidence: 99%
“…This includes optimized design of balconies, which can greatly influence the facade noise levels (Echevarria Sanchez et al, 2016;Badino et al, 2019). Generally, balconies on building facades have been found to provide significant protection from a noise source on the ground or on the roadway (Hossam El Dien and Woloszyn, 2005;Tang, 2017), although the protective effect can be weakened by reflective balcony ceilings (Hossam El Dien and Woloszyn, 2004;Wang et al, 2015). The shape and placement of balconies also have to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Tang conducted a thorough review on the available natural ventilation-enabling noise control devices and grouped them into five categories, as follows: protrusions (such as fins, lintels, and screens), resonant devices, balconies, active noise control (sound cancellation) and plenum windows/double-wall structures with staggered air inlets and outlets; the final category is the most promising one (Tang, 2017). Sakamoto et al found that protrusions are not effective because their noise reduction is relatively small (1-10 dB) and they require large sound incidence angles (more than 80°) to achieve an insertion loss above 4 dB (Sakamoto, Ito, & Asakura, 2008).…”
Section: Theoretical Reviewsmentioning
confidence: 99%
“…A study conducted by Lee found that plenum windows with 75-mm air cavities could have sound transmission class (STC) 30-40, which is considered very good (Lee, 2016). Tang concluded his review by stating that plenum types are the most promising noise-reducing ventilated windows for tropics and subtropics, and they can be developed further by combining them with other sound attenuation devices working based on resonant and noise-cancelling principles (Tang, 2017).…”
Section: Theoretical Reviewsmentioning
confidence: 99%